"Oxygen with Love" and Diode Laser Treatment Decreases Comorbidity and Avoidable Blindness due to Retinopathy of Prematurity: Results Achieved in the Past 12 Years - Jose Luis Garcia-Serrano; José Uberos Fernández; Roberto Anaya-Alaminos; Antonio Jerez-Calero; José Francisco Padilla-Torres; Maria Carmen Ramírez-Garcia; Raquel Piñar-Molina (Elsevier, 2013)
To determine whether the "Oxygen with Love" (OWL) and diode laser treatment provided in a neonatal intensive care unit has reduced the risk of avoidable blindness caused by retinopathy of prematurity (ROP) over the past decade. Materials and methods: A prospective observational cohort study was performed, in which 351 infants were examined for ROP. The inclusion conditions were as follows: preterm infants, birthweight <1500 g or <32 weeks' gestational age, and birth between 1 Jan 2000 to 31 August 2012. From mid-2009, the OWL program was implemented and the ventilation protocols for such infants were amended. We tested whether the incidence of unfavorable structural outcomes of ROP had decreased following these changes. Results: From 2004 to 2012, the survival rates of younger children increased (p < 0.003). From 2005 to 2012, laser treatment rather than cryotherapy was applied, and the incidence of unfavorable structural outcomes of ROP fell from 13% to 5.6% (not significant). From 2009 to 2012, the incidence of ROP decreased from 55% to 29% (p < 0.002). From 1 August 2009 to 31 August 2012, there was less need for ablative treatment for premature infants, with the rate falling from 11.81% to 3.9% (p < 0.03). This improvement was significantly associated with a reduction in the number of days of intubation (p < 0.0017), lower rates of sepsis (p < 0.003), and improvements in postnatal weight gain (p < 0.0002). Conclusion: The introduction of the OWL program, together with lower rates of sepsis, improvements in postnatal weight gain, and the use of diode laser treatment, has reduced the incidence of unfavorable structural outcomes of ROP.